Perspectives from neuro-oncology providers on patient access to electronic records: a survey study - Keng Lam; Cheuk Hong Leung; Zaid Soomro; Chetna Wathoo; Shiao-Pei Weathers (CNS Oncology)
Aim: To evaluate the neuro-oncology providers' experience with patient online access to electronic records. Methods: Cross-sectional survey for physicians and advanced care providers within the field of neuro-oncology in the USA. Results: 65 providers completed the survey, from all major regions of the USA. 58% reported that at least once per month, patients contacted them outside of an office visit about provider notes or a laboratory or imaging finding accessed online. 54% of providers did not think that all laboratory results should be released automatically, and only 25% of providers thought that all radiology reads should be released immediately. 97% thought that some patients suffered substantial distress viewing test results prior to appointments. Qualitative responses aligned with the quantitative results. Conclusion: Most neuro-oncology providers are concerned about the immediate release of laboratory and imaging findings to patients without guidance.